Serum concentrations of polybrominated biphenyls (PBBs), polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) in the Michigan PBB Registry 40 years after the PBB contamination incident - Che-Jung Chang (Environment International, 2020)
Widespread polybrominated biphenyls (PBBs) contamination occurred in Michigan from 1973 to 1974, when PBBs were accidentally substituted for a nutritional supplement in livestock feed. People who lived in the state were exposed to PBBs via several routes including ingestion, inhalation and skin absorption. PBBs sequestered in lipid-rich matrices such as adipose tissue, are slowly eliminated after entering the human body, and can also be transferred from a mother to her offspring through the placenta and breastfeeding. Due to the long biological half-lives of PBBs, as well as concerns from the exposed community, biomonitoring measurements were conducted from 2012 to 2015. Because of their similar structures, serum PBBs, polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs) were all measured 40 years after the PBB contamination incident (N = 862). The serum PBB-153 levels among the original highly-exposed groups (i.e., chemical workers, the family of chemical workers, and individuals who lived on or received food from the contaminated farms) remains significantly higher than other Michigan residents. Several predictors such as sampling age, sex, and smoking status were significantly associated with the serum levels of some persistent organic pollutants (POPs). Higher average values and also wider ranges of serum POP levels were found in this study compared to the National Health and Nutrition Examination Survey (NHANES), with the most substantial difference in serum PBB-153. This was true for all groups of Michigan residents including those who were not part of the above-described highly-exposed groups. Moreover, the people born after the contamination incident began also have higher serum PBB-153 levels when compared with more recent NHANES data (2010–2014), which suggests potential intergenerational exposure and/or continued environmental exposure following the contamination period. Keywords: Polybrominated biphenyls (PBBs), Polychlorinated biphenyls (PCBs), Polybrominated diphenyl ethers (PBDEs), Persistent organic pollutants (POPs), Michigan PBB Registry, Biomonitoring